2005
DOI: 10.1111/j.1471-4159.2005.03462.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of spinal cord injury‐induced central neuropathic pain

Abstract: Central neuropathic pain (CNP) is an important problem following spinal cord injury (SCI), because it severely affects the quality of life of SCI patients. As in the patient population, the majority of rats develop significant allodynia (CNP rats) after moderate SCI. However, about 10% of SCI rats do not develop allodynia, or develop significantly less allodynia than CNP rats (non-CNP rats). To identify transcriptional changes underlying CNP development after SCI, we used Affymetrix DNA microarrays and RNAs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
130
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 84 publications
15
130
2
1
Order By: Relevance
“…In pathological conditions of spinal cord injury, a biphasic change in AQP4 expression levels was demonstrated in astrocytes, revealing early down-regulation and subsequent up-regulation of the protein (Nesic et al 2006). AQP4 up-regulation associated with activated astroglial cells suggests strong implications for AQP4 in the development of neuropathies like cell swelling or persistent pain progression (Nesic et al 2005;Nagelhus et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions of spinal cord injury, a biphasic change in AQP4 expression levels was demonstrated in astrocytes, revealing early down-regulation and subsequent up-regulation of the protein (Nesic et al 2006). AQP4 up-regulation associated with activated astroglial cells suggests strong implications for AQP4 in the development of neuropathies like cell swelling or persistent pain progression (Nesic et al 2005;Nagelhus et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The GFAP expression increased and reached its maximum level after 3 days, and then decreased to the control level over the remainder of the 2-week experiment. Data from a mammalian CNS injury showed that mouse GFAP expression increased significantly after SCI, reaching a peak at 4 weeks and persisting for months [43][44][45][46]. The effect of reactive astrocytes in mammalian CNS after injury seems to be two-fold: reactive astrocytes play a beneficial role, such as the promotion of synaptic regeneration in the acute stage after CNS injury, but later act as inhibitors of CNS regeneration [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we and others have studied the changes in gene expression levels in the dorsal root ganglia and in the spinal cord after nerve injury. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] When the human genome is mapped for genes controlling CPSP, these comparative studies will facilitate identifying conserved loci for CPSP in mice and humans. This knowledge will become important when developing novel analgesics in mice, which share CPSP genetic ''architecture'' similar to that in humans.…”
Section: Pain Genetics: Ongoing Studiesmentioning
confidence: 99%